2018
DOI: 10.1002/cmdc.201800334
|View full text |Cite
|
Sign up to set email alerts
|

A Compact and Synthetically Accessible Fluorine‐18 Labelled Cyclooctyne Prosthetic Group for Labelling of Biomolecules by Copper‐Free Click Chemistry

Abstract: A new fluorine-containing azadibenzocyclooctyne (ADIBO-F) was designed using a synthetically accessible pathway. The fluorine-18 prosthetic group was prepared from its toluenesulfonate precursor and isolated in 21-35 % radiochemical yield in 30 minutes of synthetic time. ADIBO-F has been incorporated into azide-functionalized, cancer-targeting peptides through a strain-promoted alkyne-azide cycloaddition with high radiochemical yields and purities. The final products are novel peptide-based positron emission t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The resulting peptide analogue, [Dpr 3 (octanoyl), Lys 19 (triazole-ADIBO-F)]ghrelin(1-19) (13), was found to have an IC 50 value of 9.7 nM and was labeled with fluoride-18 to produce [ 18 F]13 in radiochemical yields of 64-66% and molar activities of 0.6-0.9 GBq/mmol. 82 Charron et al continued with this theme and reported a probe containing a 1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetic acid (DOTA) chelator off the C-terminal lysine residue (Figure 8), [Dpr 3 (octanoyl), Lys 19 (Ga-DOTA)]ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (14), which possessed an IC 50 value of 5.9 nM, comparable to natural ghrelin (IC 50 ¼ 3.1 nM). 58 The probe was labeled with gallium-68 in radiochemical yields of 54%-83% and molar activities of 10.2-22.8 GBq/mmol.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting peptide analogue, [Dpr 3 (octanoyl), Lys 19 (triazole-ADIBO-F)]ghrelin(1-19) (13), was found to have an IC 50 value of 9.7 nM and was labeled with fluoride-18 to produce [ 18 F]13 in radiochemical yields of 64-66% and molar activities of 0.6-0.9 GBq/mmol. 82 Charron et al continued with this theme and reported a probe containing a 1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetic acid (DOTA) chelator off the C-terminal lysine residue (Figure 8), [Dpr 3 (octanoyl), Lys 19 (Ga-DOTA)]ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (14), which possessed an IC 50 value of 5.9 nM, comparable to natural ghrelin (IC 50 ¼ 3.1 nM). 58 The probe was labeled with gallium-68 in radiochemical yields of 54%-83% and molar activities of 10.2-22.8 GBq/mmol.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
“…Another example of incorporating imaging moieties off the C-terminus of ghrelin was reported by Murrell et al 82 The authors developed a novel 18 F-prosthetic group based on an azadibenzocyclooctyne (ADIBO) scaffold and demonstrated its ability to be incorporated into biomolecules through successful conjugation to ghrelin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) with minimal effects on the binding affinity (Figure 9). The resulting peptide analogue, [Dpr 3 (octanoyl), Lys 19 (triazole-ADIBO-F)]ghrelin(1-19) (13), was found to have an IC 50 value of 9.7 nM and was labeled with fluoride-18 to produce [ 18 F]13 in radiochemical yields of 64-66% and molar activities of 0.6-0.9 GBq/mmol.…”
Section: Molecular Imaging Agents Based On Ghrelinmentioning
confidence: 99%
“…In the beginning, we synthesized a PEG 4 ‐containing DBCO substrate ( 2 ) from dibenzosuberenone ( 1 ) following the literature [21, 22] (Scheme 1; see Scheme S1 in the Supporting Information). In the next‐step deprotection of the tert ‐Butyl ester using 20 % TFA, we noticed the product 3 and its NHS ester 4 lost the click reactivity with azide substrates surprisingly.…”
Section: Figurementioning
confidence: 99%
“…23,24 The SPANC reaction has quickly found applications that range from protein modification 25,26 and cell surface labeling, 24 to materials science 27 and radiolabelling. [9][10][11][12][13][14][15][16][17][18]28 Nevertheless, it is surprising how to date it has not found an application in the synthesis of radiolabeled nanomaterials.…”
Section: ■ Introductionmentioning
confidence: 99%